PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA TERHADAP ANAK PELAKU TINDAK PIDANA KEPEMILIKAN SENJATA TAJAM(Studi Putusan Nomor: 58/Pid.Sus-Anak/2024/PN Tjk) - Paten Nuri; Anggalana; Risti Dwi Ramasari (JOURNAL OF LAW AND NATION, 2026)
This study aims to analyze law enforcement regarding the causal factors and considerations of judges in criminal cases against children perpetrator possession of sharp weapons. The sources and types of data used are primary and secondary data. Data collection through library research and field research. The causal factors for criminal acts against children for possession of sharp weapons are social factors that contribute to juvenile delinquency, including inadequate supervision and easy access to weapons, which exacerbate the risk of violence among young people. Then the judge not only considers the applicable legal provisions, but also the principle of the best interests of the child and rehabilitative efforts, in order to prevent recidivism and support the social reintegration of children.